Pengaruh Earnings Per Share (EPS), Return on Equity (ROE) dan Debt to Equity Ratio (DER) terhadap Harga Saham pada PT. AKR Corporindo Tbk 2010 – 2025 - Jessica Sari Feriska; Fazhar Sumantri; Theysa Sahlani Pratiwi (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
This study aims to analyze the effect of Earnings Per Share (EPS), Return on Equity (ROE), and Debt to Equity Ratio (DER) on stock prices at PT AKR Corporindo during the 2010–2025 period. This research is based on the importance of financial ratio analysis as a consideration for investors in evaluating company performance and making investment decisions in the capital market. The research method used was quantitative with secondary data in the form of annual financial statements obtained from the Indonesia Stock Exchange and other supporting sources. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 20. The t-test results showed that EPS had a negative and significant effect on stock prices with a t-value of -3.155 and a significance value of 0.008, ROE had a positive and significant effect with a t-value of 2.635 and a significance value of 0.022, and DER had a positive and significant effect with a t-value of 3.877 and a significance value of 0.002. The F-test result showed an F-value of 6.467 with a significance value of 0.007, indicating that EPS, ROE, and DER simultaneously had a significant effect on stock prices. The coefficient of determination was 0.618, indicating that the variables explained 61.8% of stock price variation.